Investigation of The Machinability of AISI 52100 Bearing Steel for Surface Roughness, Tool Life and Temperature Criterions - Caydas, Ulas; Kuncan, Osman; Celik, Mahmut (Gazi Univ, 2017)
In this study, spheroidized AISI 52100 bearing steel was machined in dry and minimum quantity of lubrication (MQL) conditions. After experiments, the average surface roughness (R-a) of samples, tool flank wears (V-B) and tool - chip interface temperature (T) values were measured. The ISO DNMG 150408 - TF and DNGA 150408T IN 23 carbide and ceramic cutting tool materials were used. In the experiments, the depth of cut (a) and tool feed rate (f) factors were fixed, while the cutting speed (V), cutting tool and workpiece materials and machining conditions factors were changed in certain intervals to experimentally explore their relatively effects on the machining responses. Consequently, optimum parameter conditions were determined and evaluated for the economic machining of AISI 52100 bearing steel.
Keywords: AISI 52100 Steel; Spheroidization Heat Treatment; Tool Life; Surface Roughness